Nisin, A Probiotic Bacteriocin, Combined with Limited Chemoradiation Therapy in Head and Neck Cancer - Fu, Wendy; Kapila, Yvonne L (Archives of Clinical and Medical Case Reports, 2021)
Objective: In this case report, we describe the use of nisin Z as an adjunctive therapy in a patient diagnosed with metastatic oropharyngeal cancer. Case Report: A 57-year-old Caucasian male patient affected by metastatic oropharyngeal cancer, was prescribed neoadjuvant chemotherapy followed by weekly cisplatin chemotherapy with radiation therapy. During the initial phase of the chemoradiation therapy, the patient was hospitalized for swelling and edema in the throat and experienced other negative side effects, including nausea. The patient elected to stop recommended treatment and began taking nisin Z for 19 weeks. The patient has reported improved symptoms, including absence of pain, dysphagia, or dyspnea, and the tumor diminishing in size since taking nisin Z. Results: Nisin Z may have contributed to improvement in the patient’s symptoms, including shrinkage of the tumor and extended survival.